Evolution of the Institute of Legal Identity of Ukrainians in the Context of Global Migration Challenges in 2026 - Fursenko, Nataliia (Академічні візії, 2026)
This article presents a comprehensive study of the evolution of the institution of the legal identity of Ukrainians under the conditions of the global migration challenges of 2026. It analyzes the impact of the full-scale war, the mass outward migration of the population, European integration, and the digitalization of public administration on the transformation of legal consciousness, legal culture, and the mechanisms of interaction between citizens and the state. The article substantiates the argument that the legal identity of Ukrainians is shaped by the combined influence of the national and the European legal spaces, as well as by the development of digital forms of the legal connection between the individual and the state. The study examines theoretical and legal approaches to the concept of legal identity and identifies its place within the structure of national, constitutional, and social identity. It establishes that, under the conditions of wartime migration, the legal identity of Ukrainians acquires a transnational character, since a significant proportion of citizens are integrating into the legal systems of European Union member states while simultaneously maintaining a legal connection with Ukraine through the mechanisms of citizenship, digital governance, and participation in the country’s sociopolitical life. Particular attention is devoted to the analysis of the regulatory and legal framework that governs the processes of forming and maintaining the legal identity of Ukrainian citizens. The article examines the provisions of the Constitution of Ukraine; legislation on citizenship, the protection of the rights of internally displaced persons, and the digitalization of public administration; as well as the international legal instruments and European Union documents that establish the standards for the protection of human rights and for the temporary protection of Ukrainian migrants. Drawing on statistical data from the European Union and Ukraine, the article analyzes the scale of wartime migration and its influence on the transformation of the legal consciousness of Ukrainians. It is shown that the digitalization of public services and the development of digital governance have become important instruments for maintaining the legal connection between citizens and the state, regardless of their place of residence. The article substantiates the emergence of a new element of legal identity, namely digital legal identity. The article proposes promising directions for strengthening the institution of the legal identity of Ukrainians under conditions of global population mobility, including the improvement of citizenship legislation, the development of digital identification, the support of Ukrainians abroad, and the harmonization of national legislation with the legal standards of the European Union. The practical significance of the study lies in the possibility of applying the formulated conclusions and recommendations to the improvement of state migration policy, of legislation in the field of digital governance, and of the mechanisms for protecting the rights of Ukrainian citizens under conditions of global migration processes.